2001
DOI: 10.1007/s002390010182
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence of Orangutan Subspecies (Pongo pygmaeus)

Abstract: Abstract. Microsatellites and mitochondrial DNA sequences were studied for the two subspecies of orangutans (Pongo pygmaeus), which are located in Borneo (P. p. pygmaeus) and Sumatra (P. p. abelii), respectively. Both subspecies possess marked genetic diversity. Genetic subdivision was identified within the Sumatran orangutans. The genetic differentiation between the two subspecies is highly significant for ND5 region but not significant for 16s rRNA or microsatellite data by exact tests, although F ST estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 48 publications
(63 reference statements)
1
34
1
Order By: Relevance
“…A recent vegetation model for the region found that a continuous belt of lowland tropical rainforest should have persisted (7), and this conclusion is supported by pollen analysis of LGM river and offshore sediments from the South China Sea (8,11). However, an increasing number of genetic studies show that migration between Sumatra and Borneo was extremely limited during the LGP even though the major islands were connected for most of the last 70 kyr (25)(26)(27)(28)(29), and possible rainforest refugia were inferred using termite morphology and taxonomic groupings (10), which worked well with other estimates derived from vicariant murine rodents (27). A savanna vegetation barrier such as we interpreted from the Batu δ 13 C profile can explain such limited crossover of rainforest specialists between east and west Sundaland.…”
Section: Discussionmentioning
confidence: 96%
“…A recent vegetation model for the region found that a continuous belt of lowland tropical rainforest should have persisted (7), and this conclusion is supported by pollen analysis of LGM river and offshore sediments from the South China Sea (8,11). However, an increasing number of genetic studies show that migration between Sumatra and Borneo was extremely limited during the LGP even though the major islands were connected for most of the last 70 kyr (25)(26)(27)(28)(29), and possible rainforest refugia were inferred using termite morphology and taxonomic groupings (10), which worked well with other estimates derived from vicariant murine rodents (27). A savanna vegetation barrier such as we interpreted from the Batu δ 13 C profile can explain such limited crossover of rainforest specialists between east and west Sundaland.…”
Section: Discussionmentioning
confidence: 96%
“…[17][18][19][20][21] de Vos 22,23 has argued that the Indonesian paleoenvironmental record reveals a more recent divergence, while Harrison et al 15 hypothesized that orangutans dispersed into Sundaland during a cold phase in the late Pliocene (~2.7 mya) and fragmented at the start of the Pleistocene (~1.8 mya), becoming genetically distinct subsequent to this. Unfortunately little is known about the biogeography of Early Pleistocene orangutans, due in part to the limited fossil record, lack of securely dated sites, and ambiguity regarding the taxonomic identification of primate material.…”
Section: Introductionmentioning
confidence: 99%
“…The islands of Sumatra and Borneo were fully formed 500 thousand years ago (Kya) but were reconnected by land bridges during the two last glaciations, ∼130-200 Kya and ∼10-100 Kya, respectively (Muir et al 2000;Hughes et al 2006). Estimates of the average time to the most recent common ancestor for both populations based on mitochondrial DNA (mtDNA) and a small number of microsatellites and autosomal and X-linked loci are ∼1.5-2.5 Mya (Zhi et al 1996;Kaessmann et al 2001;Zhang et al 2001), but to our knowledge, there are no published estimates of the population split time.…”
mentioning
confidence: 99%